Learning Transformative Based Literacy and Numeration in School Base - Rahmat S. Machmud; Lisdawaty Abas; Idan I. Pakaya (Global Scientific Publishing, 2023)
Learning transformative based literacy and numeracy in elementary school lesson thematic from grades 1-6 can held with provide stimulus to student . Literacy and numeracy is Skills important thing to do owned by students school base For support his abilities in education, reach potential, and participate in public. This article will review draft learning transformative based literacy and numeracy For child school base. Learning theory transformative and conceptual literacy numeracy explained as development draft learning Because learning transformative No only transfer knowledge but also do change, esp understand literacy and numeracy.
Keywords: Learning transformative; literacy; numeracy